Onychogryphosis in tuberous sclerosis complex: an unusual feature - Xiang-chun Han; Li-qiang Zheng; Tie-gang Zheng (Sociedade Brasileira de Dermatologia, 2016)
Abstract Onychogryphosis is an acquired nail plate change. It often affects the toenail and is characterized by an opaque, yellow-brownish nail plate that is distorted, grossly thickened, elongated, and partly curved resembling a ram's horn. Tuberous sclerosis complex is a multisystem disorder associated with high rates of mental retardation, autism, cognitive impairment, behavioral problems, or seizures. Nail disease can also be associated, which is a concern to patients due to pain and nail distortion. We reported a typical tuberous sclerosis complex patient with distinctive clinical features of a ram's horn nails, which presented a great challenge to surgical treatment and nail restoration.